The SAGE handbook of sport management - Hoye, Russell 1966-; Parent, Milena M. (SAGE Publications, 2017)
"The SAGE Handbook of Sport Management draws together the best current research on the major topics relevant to the field of sports management, including leadership, gender, diversity, development, policy, tourism and media. Edited by two of the most respected figures in the field, the handbook includes contributions from leading sport management academics from Australia, Canada, New Zealand, USA, the UK and Europe."--book cover